Risk factors and comorbidities for psoriatic arthritis. Literature review - Pich-Czekierda, Aleksandra; Kotowicz, Zuzanna; Proszowska, Patrycja; Orzeł , Adrianna; Sieniawska, Daria; Madoń, Magda; Sieniawska, Julia (Journal of Education, Health and Sport, 2024)
Introduction: Psoriatic arthritis is a chronic disease involving peripheral arthritis, spondylitis, dactylitis (inflammation of the whole digit) and enthesitis. It is a disease equally prevalent in both genders. Psoriatic arthritis coexists with several conditions, including metabolic syndrome, obesity, cardiovascular disease, inflammatory bowel disease, and liver disease. The reciprocal effects of comorbidities with psoriatic arthritis are demonstrated by recent research. There are several risk factors associated with the condition that might hasten or worsen its symptoms. Aim of the Study: The purpose of this paper is to present a thorough analysis of the research that has been done on comorbidities and risk factors for psoriatic arthritis. With an emphasis on changeable elements that might impact the disease's progression, the goal is to illustrate the multifaceted nature of psoriatic arthritis. The intention is also to highlight comorbidities that need to be considered while treating a patient with the illness. Materials and methods: An analysis of papers available in PubMed and Google Scholar was performed using the following key words: psoriatic arthritis, psoriatic arthritis and lifestyle, psoriatic arthritis and comorbidities, psoriatic arthritis and cardiovascular risk, psoriatic arthritis and gastrointestinal diseases, psoriatic arthritis and physical activity, psoriatic arthritis and diet, psoriatic arthritis and alcohol, psoriatic arthritis and smoking. Conclusions: Psoriatic arthritis is a chronic disease that affects many areas of patients' lives. It is critical to consider the connections that exist between this illness and other comorbidities. In order to provide a patient with this ailment with the best care possible, variables that might exacerbate the illness's progression must also be taken into consideration. Patients' mental health should get particular attention, and lifestyle modifications should be promoted.